2021
DOI: 10.1002/admi.202101677
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobin‐Coated Solid Fluorinated Nanoparticles for 19F‐MRI

Abstract: In recent years, fluorine‐magnetic resonance imaging (19F‐MRI) has emerged as a promising diagnostic technique, complementary to traditional proton magnetic resonance imaging (1H‐MRI) and easily translatable for clinical use, providing in‐depth in vivo quantification without the use of radioactive agents. This creates a need for the development of appropriate delivery systems for highly omniphobic fluorinated probes. The use of the film‐forming protein hydrophobin (HFBII) represents a sustainable and simple me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Being solid at room temperature, established liquid PFC formulation procedures cannot be directly applied, thus requiring the development of different approaches. To date, we developed several types of colloidal formulations containing PERFECTA, which display optimal relaxation times, T 1 and T 2 and confirm its excellent suitability as 19 F-MR tracer (Figure a–h). ,, …”
Section: Superfluorinated Tracer (Perfecta)mentioning
confidence: 70%
See 4 more Smart Citations
“…Being solid at room temperature, established liquid PFC formulation procedures cannot be directly applied, thus requiring the development of different approaches. To date, we developed several types of colloidal formulations containing PERFECTA, which display optimal relaxation times, T 1 and T 2 and confirm its excellent suitability as 19 F-MR tracer (Figure a–h). ,, …”
Section: Superfluorinated Tracer (Perfecta)mentioning
confidence: 70%
“…PEG-based surfactants typically display a stealth effect to ensure stability in the physiological milieu and reduce formation of protein corona, which is necessary to minimize undesired blood clearance . However, it has been shown that PEG can lead to antibody formation, thus accelerating blood clearance, , promoting researchers to explore PEG alternatives. ,, Therefore, we explored a class of amphiphilic proteins, hydrophobins, as possible nonimmunogenic stabilizers for obtaining PERFECTA formulations with reduced sizes and stealth properties (Figure c,g) . Hydrophobin-II (HFBII) displays a highly hydrophobic patch enabling, for example, the formation of HFBII films on hydrophobic and fluorinated switching surface. This rationale was applied to disperse PERFECTA in HFBII aqueous solutions resulting in the formation of 50 nm PERFECTA solid NPs coated by a protein shell.…”
Section: Superfluorinated Tracer (Perfecta)mentioning
confidence: 99%
See 3 more Smart Citations